Different kinetics of chicken interferon-alpha signalling transduction responses following immunization of broiler chickens with different Newcastle disease virus vaccines and infection with virulent genotype VIId strain. Issue 1 (2nd January 2021) - Hassanin, Ola; Abdallah, Fatma; Ali, Haytham A.; AlGabr, Naif; Mohamed, Mahmoud H. A.
ABSTRACT: Newcastle disease virus (NDV) is a highly contagious and notifiable avian disease leading to grave economic losses in the poultry industry. Although the immune responses against NDV have been widely investigated, little is known regarding the virus interaction with the host innate immune responses. In this study, we tested the effect of different commercially applied Newcastle disease vaccines as well as virulent NDV genotype VIId on the expression pattern of the upstream regulator and downstream effector genes related to chicken interferon-alpha (chIFNα) signalling transduction pathway. Using quantitative real-time PCR analysis, mild transient induction of chIFNα-inducible genes was detected in bird spleen 72 h post-vaccination (hpv) with either live LaSota (respiratory) or VG/GA (enteric) strains. Vaccination with the enteric VG/GA strain led to stimulation of the investigated pathway as early as 24 hpv which continued up to 7 days in bird caecal tonsils. Subcutaneous injection with inactivated LaSota oil adjuvant-based vaccine led to continual stimulation of the investigated pathway up to 7 days post-vaccination (dpv). The recombinant herpesvirus of turkey (rHVT) - NDV vaccine led to remarkable stimulation of all the tested cytokines up to 17 dpv in comparison with LaSota and VG/GA NDV vaccines. Stronger but transient activation of all the tested cytokines was detected in spleens during the first 24 h post-challenge with virulent NDV (vNDV) which reduced gradually and diminished later due to the virus-induced lymphocytic depletion. This study will aid in the discovery of new approaches to control NDV.